TINJAUAN KELENGKAPAN PENGISIAN FORMULIR INFORMED CONSENT TINDAKAN BEDAH GUNA MENUNJANG STANDAR NASIONAL AKREDITASI RUMAH SAKIT (SNARS-1) HPK 5.2 DI RUMAH SAKIT BHAYANGKARA TK.II SARTIKA ASIH BANDUNG - Luqman Nul Hakim; Encep Hada (Jurnal TEDC, 2021)
Based on the results of a preliminary study at the Bhayangkara TK.II Sartika Asih Hospital in Bandung, the authors found a problem, namely that there were still incompleteness in filling out the informed consent in January 2021 by 75.04% which were filled out completely and 24.96 were filled out incompletely. In this research, the method used is descriptive research method with quantitative method approach. Data collection techniques using observation, interviews and literature study. The results showed incomplete informed consent in October-December 2020 as many as 37 forms or 18.16% which were not filled out completely and 169 forms or 81.84% were filled out completely. Standard Accreditation Assessment HPK 5.2 at Bhayangkara TK. II Sartika Asih Hospital Bandung on the assessment elements 1,2,3, and E.P 4 got a score of 10 (completely fulfilled). Suggestions put forward by the authors include: Installation of medical records reports routinely to the head of the hospital and related units about the completeness of filling out informed consent, holding regular and scheduled socialization/meetings by related parties regarding the importance of filling out informed consent forms, endeavored that every doctor or nurse surgical units are more proactive when they find an incomplete informed consent form and the hospital holds a special officer in the operating room to carry out a final examination of the completeness of filling out the informed consent before the patient is taken for action.